Pengaruh Penggunaan Abu Kayu Jati sebagai Subtitusi Semen pada Beton Pori - Kusuma, Priba Dwi; Rochmah, Nurul (CV. Information Technology Training Center - Indonesia (ITTC), 2026)
His study aims to analyze in depth the effect of teak wood ash substitution as a partial replacement for cement on the compressive strength of porous concrete. Teak wood ash was selected as an alternative material because, in addition to being abundantly available as wood waste, it also has the potential to reduce cement consumption, thereby contributing to lower carbon emissions and reduced concrete production costs. This research employed a systematic laboratory experimental method with teak wood ash substitution variations of 0%, 1%, 2%, 3%, and 5% by weight of cement. Each mixture was carefully tested to determine its effect on the compressive strength of porous concrete at 28 days of curing age, in accordance with applicable concrete testing standards. The test results showed that porous concrete without teak wood ash substitution produced the highest compressive strength of 8.32 MPa. Meanwhile, the compressive strength values for substitutions of 1%, 2%, 3%, and 5% were 6.84 MPa, 7.39 MPa, 6.84 MPa, and 5.73 MPa, respectively. These results indicate that the addition of teak wood ash tends to reduce the compressive strength of porous concrete; however, the 2% substitution variation showed the best performance among all variations. The decrease in compressive strength at higher substitution levels is presumed to occur due to the reduction in cement as the main binding material and the increase in air voids within the concrete, resulting in a less dense concrete structure. Therefore, a 2% teak wood ash substitution can be considered the optimum level for producing porous concrete that still possesses adequate strength while being more environmentally friendly and cost-effective.